Streptococcal Infections in Marine Mammals - Daniela Numberger; Ursula Siebert; Marcus Fulde; Peter Valentin-Weigand (Microorganisms, 2021)
Marine mammals are sentinels for the marine ecosystem and threatened by numerous factors including infectious diseases. One of the most frequently isolated bacteria are beta-hemolytic streptococci. However, knowledge on ecology and epidemiology of streptococcal species in marine mammals is very limited. This review summarizes published reports on streptococcal species, which have been detected in marine mammals. Furthermore, we discuss streptococcal transmission between and adaptation to their marine mammalian hosts. We conclude that streptococci colonize and/or infect marine mammals very frequently, but in many cases, streptococci isolated from marine mammals have not been further identified. How these bacteria disseminate and adapt to their specific niches can only be speculated due to the lack of respective research. Considering the relevance of pathogenic streptococci for marine mammals as part of the marine ecosystem, it seems that they have been neglected and should receive scientific interest in the future.